Explain This, Explore That: A Study of Parent–Child Interaction in a Children's Museum. Issue 5 (13th March 2019) - Willard, Aiyana K.; Busch, Justin T.A.; Cullum, Katherine A.; Letourneau, Susan M.; Sobel, David M.; Callanan, Maureen; Legare, Cristine H.
Abstract : Parents visiting a gear exhibit at a children's museum were instructed to encourage their children ( N = 65; ages 4–6) to explain, explore, or engage as usual. Instructions led to different patterns of play at the exhibit: Encouragement to explain led to greater discussion of gear mechanisms, whereas encouragement to explore led to more time connecting gears. In the explain condition, parents' questions predicted their children's discussion and further testing of gears. Questions also predicted the amount of time children spent on a follow‐up task. Parents' exploration predicted an increase in exploration by their children. These data indicate that minimal interventions impact parent–child interaction at a museum exhibit and that prompts to explore or explain uniquely influence parent and child behavior.